Changes in arm coordination and stroke parameters on transition through the lactate threshold - Figueiredo, P.; Morais, P.; Vilas-Boas, J. P.; Fernandes, R. J. (European Journal of Applied Physiology, 2013)
The purpose of the present study was to understand the energetic, biomechanical and coordinative changes occurring throughout the transition of the lactate threshold. Twelve high-level swimmers (six males and six females) performed a paced intermittent incremental protocol of 7 × 200 m (0.05 m/s increments and 30 s intervals). The stroking parameters (stroke rate and stroke length) and the index of coordination (IdC) were assessed by analysis of video recordings from aerial and underwater side-view cameras. Energy cost (C) was determined by the ratio energy expenditure/velocity. Energy expenditure was determined by measuring oxygen uptake (VO2) and blood lactate concentrations ([La-]). The swimming velocity at the inflection point of stroke rate, stroke length, IdC, VO2 , and [La-] was determined (m/s). The results showed that stroke rate, stroke length, IdC, VO2 , and [La-] all exhibited inflection point as a function of swimming velocity, and these velocities were highly correlated with the velocity at [La-]inflex (1.35 ± 0.07 m/s; R = 0.99, P < 0.001). Furthermore, these values were not significantly different (P > 0.05), and Bland-Altman plots estimations were almost unbiased. These findings seem to confirm that as swimming velocity increases and lactate threshold is surpassed, it induces changes in stroke mechanics and organization suggesting an important biomechanical, coordinative and metabolic boundary between moderate and heavy intensity domains.